(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Visceral fat is a type of fat that accumulates around the internal organs in the abdominal cavity. It is having a lot of normal physiological functions within the body and when it exceeds the normal level it leads to many diseases. Visceral fat is associated with several health conditions, including insulin resistance, Type 2 diabetes, obesity and fatty liver. A comprehensive understanding of the impact of visceral fat on the above diseases and detrimental effects of visceral fat on human health and well-being is needed. Stress has a major role in visceral fat accumulation as chronic stress can lead to increased levels of cortisol, which promotes the storage of visceral fat. Hence an integrated module which includes diet, yoga, meditation, and exercise to reduce cortisol levels and prevent visceral fat accumulation is needed. Early detection and prevention of visceral fat accumulation is of prime importance to reduce the risk of developing these health conditions. According to Ayurveda visceral fat accumulation can be considered as a result of Medodhathudushti which is the major cause of Sthoulya and Prameha. For the prevention of excess visceral fat accumulation, Ayurveda recommends certain daily routines, dietary guidelines, ethical principles and lifestyle modifications. Ayurveda emphasizes self-control, non-suppression of natural urges and maintaining a positive outlook to reduce stress levels. This paper unravels the link between obesity, insulin resistance, and fatty liver and highlights the ayurvedic principles to tackle visceral fat and its complications.